Controlled Burning and Change in Vegetation - Mohan, N. P. (Indian Forester, 1941)
Details of ground flora in 8 transects situated in burnt and unburnt Pinus longifolia sample plots are recorded both for June and September. Species peculiar to the burnt and unburnt transects are listed. Area under blanks is greater in the burnt transects which have comparatively less vegetation. Premma hevrbacea, amongst others, is peculiar to the burnt transects. It is the first attempt of work of this kind.